Bulge Oscillation Driven by Outflows of Active Galactic Nuclei. I. Fast Outflow Case - Yue-Chang Peng; Jian-Min Wang; Yu Zhao; Luis C. Ho (The Astrophysical Journal, 2025)
There is growing evidence for star formation inside outflows of active galactic nuclei (AGNs). The formed stars are injected into bulges and give rise to perturbation of bulges. In this paper, we investigate the issues of nonrotating, spherically symmetric bulges under the perturbation of fast, massive outflows with stars formed inside. We show that the potential perturbation of outflows, together with injection and dynamical friction of these stars, could drive bulge oscillations. Still, we find that nonzero radial velocity of bulges will be driven by the episodic outflows of AGNs, and after the AGN has quenched, the radial velocity will tend to zero within a timescale ~ τ _AGN , which is the AGN's lifetime. For some typical values of bulges and AGNs, we find that the expansion and contraction velocities are a few × 10 km s ^−1 for 10 ^10 M _⊙ bulges and mass outflowing rate 500 M _⊙ yr ^−1 , which would give observational signatures.